Investigation into noise problems in vehicle structure using vibro-acoustic approach - Hanouf, Zahir Ahmad; Faris, Waleed Fekry (Inderscience Publishers, 2009)
The main focus of this paper is the study of the relationship between components of vibration and noise inside the passenger cabin of a production vehicle. The noise inside automobiles is largely composed of contributions from the engine, ground and wind. The engine and tyres successively transfer the vibration via the structural connections to the body panels, which then propagates through the air to the interior of the car cabin. The analysis technique is based on the signal analysis method of sound pressure level and vibration response, and the modal analysis method of vehicle structural components. Firstly, the results were obtained by the noise contour test, which is a contour of sound pressure level, done over the horizontal cross-sectional plane inside the cabin. This was carried out under the random excitation, to predict the dominating noise frequencies. Secondly, the vibration response on the front suspension in the vertical direction under the engine excitation was studied. Finally, the modal analysis was used to determine the dynamic characteristics of every component of the vehicle body panels; this would contribute to the interior noise. It was found that the interior noise of the car vehicle is mainly caused by the excessive bending mode vibration of the front suspension and twisting mode vibration of the cross-roof beam.